TAFSIR KOMUNITAS DAKWAHTAINMENT DI TELEVISI - Robeet Thadi (JURNAL ILMIAH SYI'AR, 2013)
The presence of propaganda in television presentation focuses on how religion is packaged and presented differently. This is due to the diversity of the audience so that different packaging will bring his own appeal for the audience to watch the show propaganda. Various dynamics and issues in dakwahtainment dimunculan religious lecture programs and soap operas among the various religious communities led to the interpretation of television viewers.